Analysis of 5S Work Culture to Prepare Modeling Design and Building Information Students' Competency in Industry - Anita Nastitisari; Yoto Yoto; Marsono Marsono (Belantika Pendidikan, 2021)
Vocational High Schools have a great responsibility in preparing a competent, skilled, creative, disciplined, and professional workforce to enter the labor market. Students' abilities can be developed through education and internships, both in the classroom and workplace. Work quality and productivity can be improved by adopting the 5S culture (Seiri, Seiton, Seiso, Seiketsu, and Shitsuke). Students' performance in modeling design and building information (MDBI) competencies will be evaluated in their ability to apply the principles of the 5S work culture in the workplace. The research was conducted at the Department of Housing and Settlement Areas and the construction company CV. Cahaya Mandiri. However, due to a lack of structure and SOPs, implementing the 5S work culture in the two locations was not consistent with the accredited 5S concept. As internship students, they will give the industry the experience of habituation it needs, but this depends on their motivation and discipline.